Design of Monitoring System For Hajj Departure Schedule At Medan City Ministry Of Religion Office - Frans Adetya Harahap; M. Faisal Afiff Tarigan (Ali Institute of Reseach and Publication, 2024)
This research aims to track the departure time of prospective Hajj pilgrims from the Medan City Ministry of Religion's online platform. The research was carried out using a system built using the PHP and MySQL programming languages. Data was collected from the previous three years to obtain an estimate of the departure schedule for prospective Hajj pilgrims from Medan City. The results of the research show that the Hajj departure schedule monitoring system that was built was effectively used by the Medan City Ministry of Religion. This system makes it possible to provide more accurate departure schedule estimates based on previous historical data. Thus, this system can help prospective Hajj pilgrims to monitor departure schedules without having to come to the office.